Brominated β-Alkoxyvinyl Trihalomethyl Ketones as Promising Synthons in Heterocyclic Synthesis - Mittersteiner, Mateus; Bonacorso, Helio G.; Martins, Marcos A. P.; Zanatta, Nilo (Synthesis, 2020)
5-Bromo- and 5,5-dibromo-1,1,1-trihalo-4-methoxypent-3-en-2-ones (brominated enones) have proven to be attractive building blocks for the construction of heterocyclic and polyheterocyclic compounds bearing a trihalomethyl moiety through interesting cyclocondensation, alkylation, and cycloaddition reactions. This review compiles all of the reactions conducted with these brominated enones since they were first disclosed in 2001.1 Introduction2 Synthesis and Initial Applications3 Synthesis Using First-Generation Intermediates4 Synthesis Using Second-Generation Intermediates5 Synthesis Using Third-Generation Intermediates6 Conclusions
Keywords: brominated enones; β-alkoxyvinyl ketones; bromo enones; trifluoromethyl; trichloromethyl; heterocycles; aza-cycles